Electronic Learning Design and Its Impact on Digital Teaching Practices at Krembung Islamic Vocational School - Mohammad Nurul Yaqin; Shaleh; Imron Rasyidi (Information Technology Education Journal, 2025)
The digital revolution has brought significant changes in the world of education, including at SMK Islam Krembung which integrates technology through electronic learning design (e-learning). This study aims to analyze the electronic learning design implemented and its impact on modern teaching practices at the school. The research method used is quantitative descriptive with data collection through questionnaires distributed to teachers and students, as well as statistical analysis to measure the effectiveness and challenges of e-learning implementation. The results of the study indicate that the implementation of e-learning provides benefits in the form of increased access to information, flexibility of the learning process, and increased digital literacy of students. However, the study also found obstacles such as limited devices, varying teacher readiness, and inequality of technology access between students. In addition, instructional planning still needs to be strengthened with a more systematic approach so that digital learning can be more effective and contextual. These findings are an important reference in the development of an adaptive, applicable, and sustainable information and communication technology-based learning model at SMK Islam Krembung, to prepare a generation of competent and competitive learners in the digital era. However, this study is still limited to existing quantitative indicators and has not reached qualitative analysis that can deepen the understanding of the implementation context.